RT-ring: a small wearable device for tremulous Parkinson’s disease diagnosis in primary care - Buonocore, Jolanda; Vescio, Basilio; De Maria, Marida; Crasà, Marianna; Nisticò, Rita; Arcuri, Pier P.; Cascini, Giuseppe L.; Latorre, Anna; Quattrone, Aldo; Quattrone, Andrea (Frontiers in Neurology, 2025)
IntroductionDifferential diagnosis of rest tremor (RT) disorders is challenging, often requiring 123I-ioflupane single-photon-emission-computed tomography (DaTscan), an expensive technique not available worldwide. In the current study, we investigated the performance of a new wearable mobile device termed “RT-ring” in predicting DaTscan result in patients presenting with RT based on rest tremor inertial features.MethodsConsecutive RT patients underwent RT-ring tremor analysis, surface electromyography (sEMG), and DaTscan. The RT-ring is a miniaturized mobile device that uses machine learning based on inertial tremor data to estimate the RT pattern. This electrophysiologic tremor feature has proven to accurately predict DaTscan result. The primary outcome was the RT-ring’s performance in distinguishing patients with and without striatal dopaminergic deficit.ResultsSixty-seven RT patients were enrolled, including 42 patients with striatal dopaminergic deficit and 25 with normal DaTscan. The RT-ring showed 85.0% sensitivity, 90.9% specificity, and 87.9% balanced accuracy in predicting DaTscan result, and demonstrated 96.8% agreement with sEMG in RT pattern classification.ConclusionThe RT-ring is a promising, non-invasive, user-friendly, wearable mobile device for supporting the diagnosis of tremulous Parkinson’s disease in primary care settings, especially in low-income countries with limited access to dopamine imaging.